Pemberian Psychological Nursing Intervention Dalam Meningkatkan Kualitas dan Kepuasan Hidup Pasien Kanker: A Systematic Review - Sari, Mulat; Yona, Sri (Jurnal Ners, 2024)
Introduction: Long chemotherapy cycles and the uncertainty of cancer prognosis cause patients to experience interrelated physical and psychological pain. In some patients the psychological pain is felt to be more severe. Psychological disorders that are not treated properly will have a negative impact on the quality and satisfaction of the patient's life. One of the nursing interventions that can be carried out is providing psychological nursing intervention. Clinical studies prove that this intervention can help improve the quality and satisfaction of patient life with large clinical significance. Objective: Determine evidence based on providing psychological nursing intervention in improving the quality and life satisfaction of cancer patients. Method: The method in this research is a systematic review of several articles searched on the Proquest, PubMed, ScienceDirect, Scopus, ClinicalKey for Nursing databases. Results: There are several important things in providing psychological nursing intervention, namely time and method of administration, the ability to communicate effectively, also actions taken during psychological guidance. Conclusion: Psychological nursing intervention can help overcome psychological disorders due to treatment and improve the quality and life satisfaction of cancer patients.